Are all high-skilled cohorts created equal? Unemployment, gender, and research productivity - John P. Conley; Ali Sina Önder; Benno Togler (Uppsala University, Department of Economics, 2012)
Using life cycle publication data of 9,368 economics PhD graduates from 127 U.S. institutions, we investigate how unemployment in the U.S. economy prior to starting graduate studies and at the time of entry into the academic job market affect economics PhD graduates' research productivity. We analyze the period between 1987 and 1996 and find that favorable conditions at the time of academic job search have a positive effect on research productivity (measured in numbers of publications) for both male and female graduates. On the other hand, unfavorable employment conditions at the time of entry into graduate school affects female research productivity negatively, but male productivity positively. These findings are consistent with the notion that men and women differ in their perception of risk in high skill occupations. In the specific context of research-active occupations that require high skill and costly investment in human capital, an ex post poor return on undergraduate educational investment may cause women to opt for less risky and secure occupations while men seem more likely to double down on their investment in human capital. Further investigation, however, shows that additional factors may also be at work.
urn:nbn:se:uu:diva-181882
Keywords: J16; J24; 330; Research Productivity; Human Capital; Graduate Education; Gender Differences; Akademiker; Konjunkturelle Arbeitslosigkeit; Hochqualifizierte Arbeitskräfte; Berufseinstieg; Hochschulforschung; USA